Clinical and functional characteristics of individuals with alpha-1 antitrypsin deficiency: EARCO international registry - Miravitlles, Marc; Turner, Alice M; Torres-Duran, María; Tanash, Hanan; Rodríguez-García, Carlota; López-Campos, José Luis; Chlumsky, Jan; Guimaraes, Catarina; Rodríguez-Hermosa, Juan Luis; Corsico, Angelo; Martinez-González, Cristina; Hernández-Pérez, José María; et al. (Respiratory research, 2022)
BACKGROUND: Alpha-1 antitrypsin deficiency (AATD) is a rare disease that is associated with an increased risk of pulmonary emphysema. The European AATD Research Collaboration (EARCO) international registry was founded with the objective of characterising the individuals with AATD and investigating their natural history. METHODS: The EARCO registry is an international, observational and prospective study of individuals with AATD, defined as AAT serum levels < 11 μM and/or proteinase inhibitor genotypes PI*ZZ, PI*SZ and compound heterozygotes or homozygotes of other rare deficient variants. We describe the characteristics of the individuals included from February 2020 to May 2022. RESULTS: A total of 1044 individuals from 15 countries were analysed. The most frequent genotype was PI*ZZ (60.2%), followed by PI*SZ (29.2%). Among PI*ZZ patients, emphysema was the most frequent lung disease (57.2%) followed by COPD (57.2%) and bronchiectasis (22%). Up to 76.4% had concordant values of FEV1(%) and KCO(%). Those with impairment in FEV1(%) alone had more frequently bronchiectasis and asthma and those with impairment in KCO(%) alone had more frequent emphysema and liver disease. Multivariate analysis showed that advanced age, male sex, exacerbations, increased blood platelets and neutrophils, augmentation and lower AAT serum levels were associated with worse FEV1(%). CONCLUSIONS: EARCO has recruited > 1000 individuals with AATD from 15 countries in its first 2 years. Baseline cross sectional data provide relevant information about the clinical phenotypes of the disease, the patterns of functional impairment and factors associated with poor lung function. Trial registration www. CLINICALTRIALS: gov (ID: NCT04180319).
Keywords: Bronchiectasis; Genotype; Phenotypes; Alpha-1 antitrypsin; průřezové studie; Registries; lidé; genotyp; Pulmonary Disease, Chronic Obstructive; Registry; bronchiektazie; chronická obstrukční plicní nemoc; prospektivní studie; plicní emfyzém; Male; Cross-Sectional Studies; Prospective Studies; alpha 1-Antitrypsin Deficiency; alpha 1-Antitrypsin; registrace; deficit alfa1-antitrypsinu; mužské pohlaví; alfa-1-antitrypsin; Pulmonary Emphysema; Humans